Morphology and anatomy of Celtis iguanaea (Jacq.) Sarg. (Ulmaceae) seedling - DOI: 10.4025/actascibiolsci.v28i1.1051 - Pilati, Rosemari (2008)
Celtis iguanaea it is a typical arboreal species of ciliar forest, belonging to the family Ulmaceae. This work intends to investigate the morphology and anatomy of seedling species. The seeds used were collected from several trees, in fragments of the Semideciduous Seasonal Alluvial and Submontane Forest located on Upper Paraná River floodplain. The seeds were germinated at constant temperatures (30ºC), using germination chambers and kept under continuous fluorescent light. Seedling development occurred in a greenhouse. Anatomical analysis was made in seedlings fixed in FAA 50. The botanical material was sectioned by microtome and stained with safranin and astra blue. The seedling is phanerocotylar and epigeal, presents ramified root, developed hypocotyl, obovate and persistent cotyledons, green and hairy epicotyl and the first leaf in a shape oblong or lanceolate. Root is tetrarch or diarch. Hypocotyl has secondary growth with deep-origin periderm. Epicotyl also shows secondary growth with periderm of subepidermic origin. Cotyledons and eophyll are dorsiventral leaves with cystolith